Peningkatan Skala Percobaan (Scale Up Experiment) Pengolahan Limbah Cair Kilang Sagu secara Aerobik menggunakan Teknologi Simbiosis Mutualisme Mikroalga Chlorella sp. dan Agrobost - Khairunnisa Amanda; Fajar Restuhadi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this research was to get selected treatment of microalgae Chlorella sp. as a reducing polutan of sago liquid waste with the concentration of Agrobost and utilize symbiotic technology between the two.  This research used a complete randomized design (CRD) with 5 treatments and 3 replications.  In this research was microalgae 800 ml/L (6.110.000 cell/ml) of sago liquid waste with 5 treatments of Agrobost (0% v/v, 2% v/v, 4% v/v, 6% v/v, and 8% v/v).  The data obtained were analyzed statistically using ANOVA and DNMRT at 5 % level.  The result showed that the concentration of Agrobost had significant affect for Nitrate, Phosphate.  The treatment chosen from the result of this research was the P4 treatment showed the highest level of reduction which had the value Phospate 3,16 mg/L, Nitrate 0,3601 mg/L. Keywords: Sago liquid waste, Agrobost, microalgae Chlorella sp.